Ice surface changes during recent glacial cycles along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica. (1st December 2020) - Andersen, J.L.; Newall, J.C.; Blomdin, R.; Sams, S.E.; Fabel, D.; Koester, A.J.; Lifton, N.A.; Fredin, O.; Caffee, M.W.; Glasser, Neil F.; Rogozhina, I.; Suganuma, Y.; et al.
Abstract: Reconstructing past ice-sheet surface changes is key to testing and improving ice-sheet models. Data constraining the past behaviour of the East Antarctic Ice Sheet are sparse, limiting our understanding of its response to past, present and future climate change. Here, we report the first cosmogenic multi-nuclide ( 10 Be, 26 Al, 36 Cl) data from bedrock and erratics on nunataks along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica. Spanning elevations between 741 and 2394 m above sea level, the samples have apparent exposure ages between 2 ka and 5 Ma. The highest-elevation bedrock sample indicates (near-) continuous minimum exposure since the Pliocene, with a low apparent erosion rate of 0.15 ± 0.03 m Ma −1, which is similar to results from eastern Dronning Maud Land. In contrast to studies in eastern Dronning Maud Land, however, our data show clear indications of a thicker-than-present ice sheet within the last glacial cycle, with a thinning of ∼35–120 m during the Holocene (∼2–11 ka). Difficulties in separating suitable amounts of quartz from the often quartz-poor rock-types in the area, and cosmogenic nuclides inherited from exposure prior to the last deglaciation, prevented robust thinning estimates from elevational profiles. Nevertheless, the results clearly demonstrate ice-surface fluctuations of several hundred meters between the current grounding line and the edge of the polar plateau for the last glacial cycle, a constraint that should be considered in future ice-sheet model simulations. Highlights: Cosmogenic 26 Al, 10 Be, and 36 Cl constrain past EAIS dynamics in Dronning Maud Land. EAIS in western DML was at least 100–200 m thicker than present within last 25 ka. EAIS in western DML was at least 150–300 m thicker within the last glacial cycle. Ice-sheet thinning ∼35–120 m towards present ice sheet surface during the Holocene. Short duration of Pleistocene ice covers >200 m above regional ice at Borgmassivet.